Land Use Changes of Catalca District (1987-2016) - (:unkn) unknown (MARMARA UNIV, 2018)
Land-use has been a subject of great importance for humanity from past. Negative human effect on natural environment is increasing continuously because of rapid population growth and technological developments. Natural environment and resources will consumed and unable to use as a result of this situation. The settlement areas are expanding with the effect of population increase. Agriculture, forest and pasture areas face destruction because of unplanned enlargement of residential areas. It has become easier for human being to make changes on natural environment thanks to technological developments. This effect has been greatened particularly in the last half century. Revealing negative effects of this changing in the natural environment and land cover is one of the most important topic for human being. Catalca District, which is determined as a research are in this study, is administratively included in Istanbul Province. The study area is located between 41 degrees 5'55'' and 41 degrees 35'2'' north latitudes and 28 degrees 4'10'' and 28 degrees 34'50'' South longitudes. Total area of the study area is 1130 km(2). Black Sea from North, Silivri and Buyukcekmece districts from South, Arnavutkoy district from east, Cerkezkoy and Saray districts, which are districts of Tekirdag Province, from West are bordering the study area. In this study, the past and present land use situation of Catalca District was idendificated and change was determined. LANDSAT satellite images which are belongs to years 1987, 2000 and 2016 provided from USGS. The uncontrolled classification method was applied to these photographs through Erdas Imagine software to determine the land cover for the related land cover years.
Keywords: Land Use Change; Catalca District; Remote Sensing